1981
DOI: 10.1002/art.1780241101
|View full text |Cite
|
Sign up to set email alerts
|

Running Inhibits the Reversal of Atrophic Changes in Canine Knee Cartilage After Removal of a Leg Cast

Abstract: The effect of vigorous exercise on the reversibility of canine knee cartilage atrophy produced by immobilization OF the leg was studied. In comparison to cartilage from the contralateral control knees, cartilage from knees which had been immobilized in a cast For 6 weeks showed an increase in water content and decreases in thickness, Safranin 0 staining of the matrix, uronic acid content, and net proteoglycan synthesis. In addition, the ability OF both newly synthesized (3'S) and total tissue proteoglycans to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
2
10

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(82 citation statements)
references
References 27 publications
4
66
2
10
Order By: Relevance
“…1) and biochemical properties could be established. An optimal way of assessing the degree of OA can be debated (Pritzker et al, 2006). In this study, we utilized the traditional Mankin score to judge structural integrity of cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and biochemical properties could be established. An optimal way of assessing the degree of OA can be debated (Pritzker et al, 2006). In this study, we utilized the traditional Mankin score to judge structural integrity of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to softening of the tissue (Armstrong and Mow, 1982). Softened articular cartilage fails to resist impact forces during normal loading and this endangers the tissue to fissures and fibrillation (Palmoski and Brandt, 1981). Tissue degeneration leads to inflow of water and, thereby, to an increase in water content of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Vários experimentos descreveram que o exercício de carga moderada na cartilagem articular gera aumento da síntese e da concentração de proteoglicanas e de glicosaminoglicana 18,19 . Além disso, ele promove aumento do volume da cartilagem e adaptação da mesma ao esforço 20 e estimulando os condrócitos a produzir os elementos que compõem a matriz extracelular 13,21,22 .…”
Section: Discussionunclassified
“…These contradictory results may be explained by the difference in rigidity of immobilization. Some reported that the articular cartilage was thickened (Sood 1971), others reported that it was thinned (Palmoski and Brandt 1981), and even others reported no change in thickness (O'Connor 1997;Trudel et al 2005). These contradictory results may be explained by a lack of standard measurement sites, use of young or old animals, or use of contralateral knees as controls (O'Connor 1997).…”
Section: Discussionmentioning
confidence: 99%